2018
DOI: 10.1111/myc.12725
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dectin‐1 receptor on cytokine production by human monocytes challenged with Paracoccidioides brasiliensis

Abstract: Fungal recognition by Dectin-1 receptor triggers a series of cellular mechanisms involved in a protective activation of the immune system. In this study, we aimed to evaluate the participation of Dectin-1 receptor in the induction of IL-8, TNF-α, IL-12, IL-10 and IL-17A secretion by human monocytes activated with different cytokines, and challenged in vitro with Paracoccidioides brasiliensis (P. brasiliensis). Our results show that monocytes challenged with P. brasiliensis (Pb265) are able to produce IL-12, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 77 publications
(175 reference statements)
1
13
0
Order By: Relevance
“…In PCM, many studies have contributed to the understanding of Dectin-1 receptor functions in human phagocytes. Studies that evaluated the participation of the receptor used different protocols, demonstrating results such as receptor participation in fungal recognition, induction of effector mechanisms, and production of cytokines such as TNF- α [4, 6, 7, 911, 3537]. In experimental models of the disease, there are conflicting data showing the participation of the Dectin-1 receptor in susceptibility and in PCM resistance [5, 8, 11, 3840].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PCM, many studies have contributed to the understanding of Dectin-1 receptor functions in human phagocytes. Studies that evaluated the participation of the receptor used different protocols, demonstrating results such as receptor participation in fungal recognition, induction of effector mechanisms, and production of cytokines such as TNF- α [4, 6, 7, 911, 3537]. In experimental models of the disease, there are conflicting data showing the participation of the Dectin-1 receptor in susceptibility and in PCM resistance [5, 8, 11, 3840].…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the infection, neutrophils and monocytes are recruited to the injured site. The fungus is initially recognized by Pattern Recognition Receptors (PRRs), and among them, the Dectin-1 receptor, a member of the C-type lectin-like receptors (CLR) can bind specifically to β -1,3 glucans in the fungal cell wall [49]. The latest studies have characterized the different activation pathways of the Dectin-1 receptor in response to P .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It recognizes β-glucan, present in the fungal cell wall, and therefore participates in the recognition of many fungal species, including P. brasiliensis ( Balderramas et al, 2014 ; Feriotti et al, 2015 ; Loures et al, 2015 ; Bachiega et al, 2016 ). Recently, Romagnolo et al (2018) demonstrated that this receptor participates in cytokine secretion by monocytes when stimulated in vitro with P. brasiliensis 265 isolate. Our results show that this receptor is not involved in ArtinM activation of neutrophils infected with Pb18 isolate.…”
Section: Discussionmentioning
confidence: 99%
“…The PRRs could be intracellular cytoplasmic or extracellular transmembrane receptors [11,15], and their bond with the PAMPs triggers many processes including the actuation of the adaptive immune response. For instance, the detection of PAMPs by Dectin-1 CLR modulates the uptake of the microorganisms via phagocytosis, leading to the production of inflammatory cytokines such as IL-12 [15,16], a fundamental cytokine involved in the activation of T Helper 1 (Th1) cells [1]. Indeed, the activation of PRRs initiates signaling cascades that promote the transcription of targeted gene encoding for cytokines, interferons, pro-inflammatory or microbicide proteins [17,18].…”
Section: Innate Immunitymentioning
confidence: 99%